Optimistic credit rating and its influence on corporate decisions: evidence from Korea. Issue 5 (2nd September 2020) - Cho, Hyungjin; Han, Seung-Youb; Oh, Seungbin; Sunwoo, Hee-Yeon
Abstract: Credit rating agencies have often been a target for criticism due to their inaccuracy and untimeliness. This paper sheds light on this issue by examining how an optimistic credit rating influences corporate decisions. We use Korean corporate credit ratings and construct the measure of credit rating optimism as the deviation of the actual ratings from benchmark ratings based on US corporate ratings. We find that rating optimism has a negative association with cost of debt and a positive relation with debt financing and investment. We also find that a positive relation between investment and future performance is weaker for firms with optimistic ratings. This finding suggests that inaccurate credit ratings would damage efficient capital allocation in the capital market.